Modeling strategic-knowledge-resource management based on individual competencies in SMEs - Justyna Patalas-Maliszewska; Martin Hochmeister (Contemporary Economics, 2011)
A number of publications have dealt with the correlation between knowledge-management capability a nd competitiveness. In the article describing human resources as strategic-knowledge resources, which is motivated by: the concept of effective management of resources in an organization (Sirmon and Hitt, 2003), an enterprise's unique potential in the form of knowledge and experience (Barney, 1995), and the concept of competence management (Hamel and Prahalad, 1994). This study describes competence and resource management, sharing in the collaborative development and implementation of strategic-knowledge-resource management in SMEs. In this context, strategic-knowledge resources are defined in such a way as to be incorporated into a model of strategic-knowledge-resource management.
Keywords: 330; strategic-knowledge resources; competence management; resource management